The analysis of wing performance for reconnaissance UAV - Zulkifli, Yusof (2009)
Through decade, the needs of the aircraft technologies are quite demanding and most of the demands came from the military and civil. The need of the technologies in nowadays life has evolving it into various types of shapes and design according to each task of work that needs to be handled. The aircraft can be classified into two common types, which are manned aircraft and unmanned aircraft. The unmanned aircraft is commonly known as the unmanned aerial vehicle or UAV. The purpose of UAV is to assist and complete the work that human cannot handle such as the bushfire surveillance. In this thesis, a mini UAV that capable to assist the work of reconnaissance and surveillance was designed and developed. The UAV should be able to complete certain parameters that already decided before the project was conducted. The main criterion of this UAV as to assist the given task is to have a perfect performance, which is having a smooth flight operation. To achieve the smooth flight operation, the main concern is to have perfect wing configuration. Therefore, the focus and purpose of this project is to analyze and choose the suitable wing parameters for the mini UAV. As the project develops, the UAV should have a 2 m wing span, 1.2 m fuselage length and 3.8 kg takeoff weight. It is quite light and easy to lost control. To avoid this problem, it is important to calculate where to put the wing onto the fuselage and which airfoil should be used for the wing. If the selection are made carelessly, the UAV probably cannot fly or can fly but in a bad condition. The analysis of the wing parameters was made using certain software that capable to act as the virtual wind tunnel. The best selection of the wing will be modeled using the CAD program as the final results of this project.